Proceedings of the 2nd International Colloquium on Sports Science, Exercise, Engineering and Technology 2015 (ICoSSEET 2015) - Ismail, Shariman Ismadi; Sulaiman, Norasrudin; Adnan, Rahmat (Springer Nature Singapore : Imprint: Springer, 2016)
The proceeding is a collection of research papers presented at the 2nd International Colloquium on Sports Science, Exercise, Engineering and Technology (ICoSSEET2015), a conference dedicated to address the challenges in the areas of sports science, exercise, sports engineering and technology including other areas of sports, thereby presenting a consolidated view to the interested researchers in the aforesaid fields. The goal of this conference was to bring together researchers and practitioners from academia and industry to focus on the scope of the conference and establishing new collaborations in these areas. The topics of interest are in mainly (1) Sports and Exercise Science (2) Sports Engineering and Technology Application (3) Sports Industry and Management.